Characterization of novel extremely extended regime in conductive rod-like polyaniline nanobrush-covered poly(ethylene glycol) single crystals. (September 2016) - Agbolaghi, Samira; Nazari, Maryam; Abbaspoor, Saleheh; Gheybi, Homa; Abbasi, Farhang
Graphical Abstract: Highlights: The fourth regime of brushes was innovated for PANI-covered single crystals. Three ordinary regimes for coily brushes were compared with the fourth regime. The strength of oxidant and the morphology of nanofibers did not affect the brush regimes. The brush regimes were judged based on the slopes of 1/dc versus Tc graphs. Abstract: The fourth regime of polymer brushes was innovated for first time based on conductive rod polyaniline (PANI) brush-covered polyethylene glycol (PEG) single crystals. The three ordinary regimes for coily brushes (i.e., non-interaction, crossover, and highly stretched regimes) were also investigated and compared by the novel extremely extended regime coined for the rod PANI nano-brushes. It was revealed that in the conductive rod polymer brushes, the type of oxidant (ammonium peroxydisulfate (APS) and potassium hydrogen diiodate (PHD)), uniformity (in PEG5000 - b -PANIn and PANIn - b -PEG6000 - b -PANIn single crystals) or dispersity (in PANIn - b -PEG35000 - b -PANIn single crystals) of arranged nanofibers diameter wise, and the morphology of tethered nanofibers on the crystalline substrate surface did not affect the brush regimes. We demonstrated that the equations of the substrate thickness, tethering density and reduced tethering density, which were quite applicable for coily brush systems, did not satisfy the conductive rigid PANI brushes. In these systems, the thicknesses were directly obtained from the interface distribution function (IDF) of small angle X-ray scattering (SAXS) analyses, and the brush regimes were judged based on the slopes of the reciprocal of substrate thickness (1/dc ) versus crystallization temperature (Tc ) graphs.